PENGARUH PESAN KAMPANYE #SUKINRECYCLESTATION TERHADAP CITRA MEREK SUKIN - Moniq Tesalonika Hutabarat (2023)
The growth in the use of beauty and skincare products that has increased every year has impacted an increase in the amount of waste containers for beauty and skin care products. Sukin as a brand of skin care products attempts to overcome this problem by creating a waste recycling campaign of skincare products called #SukinRecycleStation. A campaign is one of the ways to build a positive reputation or image in the presence of general public with the aim of building public trust and acceptance. This research aims to find out whether there is an influence from #SukinRecycleStation campaign message on the formation of Sukin's brand image and how big is the influence generated. This research was conducted using a type of quantitative explanative approach and the Elaboration Likelihood Model theory. The sample of this research was 100 people who are followers of the @sukinskincare_idn account. The results obtained in this research showed that there is a significant influence between #SukinRecycleStation campaign message on the formation of Sukin brand image. The #SukinRecycleStation campaign created a positive brand image and made Sukin a more trusted brand by the public.